Podjetniška demografija in dinamika podjetij različnih tehnoloških ravni, znanja in razvojnih faz: Slovenski podjetniški observatorij 2024 - Bradač Hojnik, Barbara; Rus, Matej; Močnik, Dijana (University of Maribor Press, 2025)
Business Demographics and the Dynamics of Companies With Different Levels of Technology, Knowledge and Development Stages: The Slovenian Entrepreneurship Observatory 2024. The Slovenian Entrepreneurship Observatory 2024 provides a comprehensive analysis of entrepreneurial demographics and the dynamics of companies of different technological levels, skills and development stages. In the first part of the survey, we examined the key demographic characteristics of Slovenian enterprises, including their number, size, revenues, labour costs and value added, disaggregated by industry, region and size class. The second part of the study focuses on firms with different levels of technology intensity and knowledge-intensive services, with an emphasis on comparing Slovenia with the EU. We have specifically analysed firms at different stages of their life cycle in order to identify their competitive advantages, development challenges and opportunities for further growth and innovation. Based on the findings, we have provided strategic orientations for improving the support environment, fostering innovation, digital transformation and internationalisation of Slovenian companies, which are key to the long-term competitiveness of the economy.